Toughening tetrafunctional epoxy resins with thermoplastics - Gilbert, A. H. (Cranfield University, 1988)
The study described in this thesis examines how modification with different thermoplastics affects the structure and properties of a tetrafunctional epoxy re5ín_ Polyetherimide (PEI) is found to give the best improvement in fracture properties without loss in Youngs Modulus and the PEI/epoxy system is used as the basis for further study. The influences of PEI concentration, initial cure temperature, test temperature and the presence of a second thermoplastic additive, are investigated. The information provided gives insight into the likely mechanisms of toughening in tetrafunctional epoxy/thermoplastic blends. Flory-Huggins Lattice Theory is used to describe miscibility behaviour for a number of curing thermoplastic/epoxy blends and the predictions compared with the actual morphologies observed. Further, the sensitivity of the expected miscibility behaviour to fluctuations in Flory Huggins interaction parameter X12 and number-average molecular weight Mn of the thermoplastic, is considered. Dynamic mechanical analysis is used to monitor the changing viscoelastic properties of curing thermoplastic/epoxy blends, allowing investigation of the way different thermoplastics influence the state transformation profile of a curing epoxy resin.